Speak to Succeed: Psikoedukasi Pelatihan Presentasi untuk Meningkatkan Komunikasi Mahasiswa Akhir dalam Dunia Kerja - Syam, Rahmawati; Bakar, Resekiani Mas; Zahrah, Zahrah; Zalsabila, Zeika; Singkali, Yemima Dirma (Pakis Journal Institute, 2025)
Final year students or often referred to as final students are a group that is in an important transition period from the academic world to the world of work. This study aims to improve the communication skills of final year students in the world of work. The method used in this research is interactive lectures, with an experimental design of One Group Pre-test-Post-test Design, which is an activity that gives a pre-test before being given treatment and then gives a post-test after giving treatment to 23 final students of Makassar State University. The results showed that participants experienced an increase in knowledge, understanding, and confidence in making presentations, with significant differences (p<0.005) based on the Wilcoxon signed rank non-parametric test. This training can help final students in preparing themselves to compete professionally in the world of work.